(3cJGH bSWGS GdeYGOdIs - (3YR GdOjf EHQGgje Hf YHO GdhgGH Hf Ydj GdTGaYj, CHh GdeYGdj , GdYRjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CMGW Hcd TF Ydeg CeG HYO aEf GdYdhe GdQjGVjI JQJbi Edi CUfGa cKjQI dcf CfaYgG Ydhe GdMSGH GdJi jMJGL EdjgG LejY GdfGS s
(3BNQgG (B:s
(3Pdc GdeNQL CYfi ef eGFI hKdGKI hSJjf Cda Cda hGMO hYTQjf CdakG hKeGfi eGFI hCQHYI hYTQjf LRAkG Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs